An integrated fatigue assessment approach of rail welds using dynamic 3D FE simulation and strain monitoring technique - Shi, Xiaopeng (2022)
Stress concentration induced by geometry irregularity was found near the weld toe of rail welded joints, leading to high risk of fatigue crack initiation. In this research, an integrated fatigue assessment method of rail welds based on the 3D dynamic finite element method (FEM) and onsite strain monitoring data has been developed. The 3D FEM considering wheel-track interaction has been built and the extracted stress and deformation results was analyzed using an implicit-explicit sequence approach. The FEM model was then validated and calibrated by strain monitoring results on a test track from strain gauges attached near the rail welds. A comprehensive investigation of fatigue behavior for rail welds under the dynamic loading condition has been conducted and it was found that the tensile peaks due to ‘reverse bending’ of the rail have a critical effect on the weld fatigue crack initiation. A further study of fatigue risk assessment using multi-axis fatigue theory revealed that the crack initiation risk is high for head-to-web transition region in gauge side.